Menstrual tampons and vaginal pessaries: regulation of intravaginal medical devices by the US FDA - Pollard, Colin M. (Frontiers in Reproductive Health, 2023)
Menstrual tampons and vaginal pessaries are medical devices that are inserted into the vagina to achieve their effect. Women have used menstrual tampons for decades to manage menstrual bleeding. Likewise, women have used vaginal pessaries for decades as a nonsurgical option for the management of urinary incontinence and pelvic organ prolapse. These devices can be inserted intravaginally and removed, repeatedly, for years. In general, FDA considers both tampons and pessaries to be safe and effective medical devices. Under a statutory risk-based classification scheme, these products are regulated by the Center for Devices and Radiological Health (CDRH), part of the Food and Drug Administration (FDA), to ensure their continued safety and effectiveness. This article provides an overview of how FDA regulates these products. For the purposes of this discussion, this article will use the terms "medical device", "device" and "product" interchangeably. The article also uses the two terms, "manufacturer" and "developer", interchangeably.The statutory foundation of medical device regulation is a 3-tiered risk-based classification system. Every medical device is classified according to its specific risks to health, from low to high, and each classification level establishes a set of controls from which FDA chooses